Different Impacts of Metabolic Syndrome Components on Insulin Resistance in Type 2 Diabetes - Chung-Hua Hsu (International Journal of Endocrinology)
Objective. To examine the different impacts of MS components on insulin resistance in type 2 diabetes. Methods. A number of subjects (144) who met the criteria of (1) age between 30 and 75 years, (2) had type 2 diabetes for more than one year, and (3) taking gliclazide and metformin for more than 6 months were enrolled. All subjects were assigned to one of the four HOMA index categories. The HOMA index quartile 4 denotes the highest insulin resistance. The main outcome evaluated is the odds ratios (ORs) of different MS components on HOMA index quartile 4. The characteristics in HOMA index quartiles and groups of nonmetabolic syndrome (NMS; number of components < 2), metabolic syndrome A (MSA; number of components = 2), and metabolic syndrome B (MSB; number of components > 2) were also evaluated. Results. The results showed that both MSA and MSB groups had higher ORs (5.9 and 13.8 times, resp.) than the NMS group; and that subjects with large waist circumference (LWC) and high triglyceride (HTG) level have higher ORs (6.1 and 2.6 times, resp.) in developing higher insulin resistance than normal control subjects. Conclusion. Type 2 diabetic patients with greater number of MS components have higher ORs in developing increased insulin resistance.